T cell‐mediated induction of thymic stromal lymphopoietin in differentiated human primary bronchial epithelial cells. Issue 7 (July 2014) - Hui, C. C. K.; Murphy, D. M.; Neighbour, H.; Al‐Sayegh, M.; O'Byrne, S.; Thong, B.; Denburg, J. A.; Larché, M.
Summary Background Inhaled peptide challenge has been shown to induce T cell‐mediated, isolated late asthmatic reaction (LAR), characterized by recruitment of CD4+ T cells and increased levels of thymus and activation‐regulated chemokine (TARC; CCL17). Epithelial‐derived thymic stromal lymphopoietin (TSLP) has been shown to modulate dendritic cell function to promote TH2 responses via CCL17 production. Objectives To elucidate the mechanisms involved in allergen‐specific T cell‐induced LAR and recruitment of CD4+ T cells by examining the effects of T cell‐derived factors on the induction of TSLP in primary bronchial epithelial cells (PBEC). Methods PBEC grown at air–liquid interface from healthy individuals and patients with asthma were stimulated with double‐stranded RNA (dsRNA) or supernatants from activated allergen‐specific T cells. TSLP was measured in PBEC culture supernatants. Neutralizing antibodies and signalling inhibitors were used to examine the mechanisms responsible for the induction of epithelial‐derived TSLP. The functional activity of PBEC‐derived TSLP was measured using a bioassay involving the induction of CCL17 production from monocyte‐derived dendritic cells (moDC). Results Both dsRNA and allergen‐specific T cells induced enhanced TSLP secretion from asthmatic PBEC compared to healthy PBEC. Activated PBEC culture supernatant induced TSLP‐dependent CCL17 production from moDC in a manner related to clinical asthmatic status. IL‐1β, IL‐6, and CXCL8, rather than TH2 cytokines (IL‐4/5/13), appeared to be the principle mediators of allergen‐specific T cell‐dependent induction of epithelial‐derived TSLP, which was regulated by the MEK, MAPK, and NFκB pathways. Conclusion and Clinical Relevance Our data reveal a novel effect of allergen‐specific T cells as a positive regulator of TSLP production by epithelial cells, suggesting T cell–airway epithelium interactions that may lead to maintenance and amplification of allergic inflammation. TSLP is currently a candidate for therapeutic intervention in asthma, but the factors that drive TSLP expression (T cell‐derived factors) may be equally relevant in the treatment of allergic inflammation.